An Investigation of Teaching English Grammar through Distance Learning at SMAN 1 Samarinda - Agitha Martha Laura; Weningtyas Parama Iswari; Maria Teodora Ping (Faculty of Teacher Training and Education, Mulawarman University, 2021)
The purposes of this study were to know how the teacher teaches English grammar through distance learning and investigate the problems during implementation of teaching English grammar through distance learning. The design of this study was qualitative research design which was characterized by a case study. The participant was selected through purposive sampling. The data were analyzed by using the interactive analysis model. The researcher used the triangulation by data source, triangulation by method, and triangulation by theory to check the validity and reliability of this study. The findings revealed that the English teacher applied teaching grammar in context, inductive and deductive approach and integrated grammar with language skills. In addition, the English teacher used flipped-classroom model a form of blended learning that combines synchronous and asynchronous online learning with WhatsApp, Google Meet, and Google Classroom as the teaching platforms. In its implementation, the English teacher faced some problems in the process of teaching English grammar through distance learning. Those problems were student discipline, limited time, teacher’s extra workload, distance between teacher and students, classroom management and technical problem. In conclusion, teaching English Grammar through distance learning can be conducted and maximized by having well preparation on learning activities, well communication and collaboration between the teacher and students in teaching ang learning process to achieve the learning objectives.